2021
DOI: 10.1080/21645515.2021.1936859
|View full text |Cite
|
Sign up to set email alerts
|

15-year experience with rotavirus vaccination in Mexico: a systematic literature review

Abstract: A systematic review was conducted in Mexico to consolidate and evaluate evidence after 15 years of rotavirus vaccination, according to the National Immunization Program. Five databases were screened to identify published articles (January 2000-February 2020) with evidence on all clinical and epidemiological endpoints (e.g. immunogenicity, safety, efficacy, impact/effectiveness) of rotavirus vaccination in Mexico. Twenty-two articles were identified (observational studies including health-economic models: 17; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The most prevalent sequences belonged to the Reoviridae and Caliciviridae families, which are the most common agents associated with diarrhoea among children. Epidemiological studies of Rotavirus illness worldwide, have revealed a similar prevalence in children from industrialized and less developed regions of the world, including Mexico, and it seems that Norovirus (Caliciviridae) illness has a similar prevalence in children from these regions, as well [41][42][43][44][45]. Other sequences that were found among our children included Mamastrovirus 1, which has been associated with approximately 5% of diarrheal episodes in Spanish children < 5 years old [46], while Astrovirus MLB1 was identified in 6% of Kenyan children with diarrhoea [46,48].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent sequences belonged to the Reoviridae and Caliciviridae families, which are the most common agents associated with diarrhoea among children. Epidemiological studies of Rotavirus illness worldwide, have revealed a similar prevalence in children from industrialized and less developed regions of the world, including Mexico, and it seems that Norovirus (Caliciviridae) illness has a similar prevalence in children from these regions, as well [41][42][43][44][45]. Other sequences that were found among our children included Mamastrovirus 1, which has been associated with approximately 5% of diarrheal episodes in Spanish children < 5 years old [46], while Astrovirus MLB1 was identified in 6% of Kenyan children with diarrhoea [46,48].…”
Section: Discussionmentioning
confidence: 99%